Kulit Manggis Menghambat Aktivasi Nuclear Factor ?B (NF-?B) dan Menurunkan Ekspresi ICAM-1 pada Tikus dengan Diet Tinggi Kolesterol - H Hendarto; Mohammad Saifur Rohman; Djanggan Sargowo (The Indonesian Heart Association, 2013)
Background: Atherosclerosis is widely viewed as an inflammatory disease with hypercholesterolemia being a dominant underlying risk factor. This study aimed to determine the effect of mangosteen pericarp in inhibition of NF-?B activation and ICAM-1 expression in rat fed with high cholesterol.Methods and Results: Various doses of crude extract mangosteen pericarp were administered to the high fat diet wistar rats and the activity of NF-?B measured by immunohistochemistry to assess nuclear NF-?B expression and the ICAM-1 expression. The high fat diet resulted significant increased serum LDL levels. Increased nuclear NF- ?B activation and ICAM-1 expression were also observed in high fat diet rats in concurrence with increased serum LDL. The inhibitory effect on NF- ?B activity and ICAM-1 expression was observed when 400 mg of mangosteen pericarp crude extract was administered and even showed a higher inhibitory effect in 800 mg of mangosteen pericap treated rats. The 800 mg extract treatment resulted in decreased ICAM-1 expression similar to those of non high fat rats.Conclusion: The administration of 800 mg mangosteen pericarp crude extract significantly inhibited NF-?B activation and reversed the expression of ICAM -1 to the normal level in high cholesterol diet rats.